Eloquent spaces: meaning and community in early Indian architecture - Kaul, Shonaleeka (Routledge, Taylor & Francis Group, 2019)
Introduction : towards a semantics of architecture / Shonaleeka Kaul -- Form, space, and consciousness : architectural principles in the vastushastras / Bettina Sharada Bäumer -- Breathing life into monuments of death : the stupa and the Buddha body in the socio-ecological landscape of Sanchi / Julia Shaw -- Spatial and architectural constructs of tantric Buddhist mandalas : a cognitive approach / Pranshu Samdarshi -- The old temple of Basgo : a hypothesis on the superimposition of 'celestial assembly' on sculpture and sangha / Gerald Kozicz -- Temple and territory in the Puri Jagannath imaginaire -- Manu Devadevan -- Stepwells of western India : Rani ki vav at Patan / Rabindra Vasavada -- Outer places, inner spaces : constructing the gaze in Chola Chidambaram / Aleksandra Wenta -- Interpreting public space in the Jaina basadis of Moodabidri / Pratyush Shankar -- On the water's edge : tracing urban form in old Srinagar / Munishwar Nath Ashish Ganju.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte; Architektur; Indien